Traditional knowledge of medicinal orchids in different parts of India - Siddhartha Sankar Biswas; N S Kalaivanan
Traditional knowledge of medicines gets transferred from generation to generation among the tribal people verbally. Since recent past some ethnobotanists started scientific documentation of it. Beside other plants, orchids also kept their deepfootprint in traditional medicines. India is a country of orchid richness with 1300 orchid species, out of those approximately 250 orchid species are being used in tribal, Ayurvedic and Unani system of medicine. In spite of having high medicinal potential, very often orchids are ignored as medicinal herbs, and emphasized as ornamental plants in India. Use of orchids in the field of medicine can draw a lot of economic benefits to the drug development industries and socioeconomic benefits to the orchid farmers. For that a compiled source of information about traditional knowledge on medicinal potential of orchids can be a good source of reference. The present review can serve the purpose